INTERACTION STRATEGIES IN THE SKILL AND CONTENT COURSES IN EFL CLASSES - A. Dzo’ul Milal; Tristy Kartika Fi’aunillah; Ramadhina Ulfa Nuristama; Raudlotul Jannah; Sufi Ikrima Saadah (Езиков свят)
Studies to reveal the factors contributing to the effectiveness of language instruction are still underway. This study disclosed the phenomenon in EFL classes focusing on the interaction strategies in skill and content courses, which use English as the target language. This study uses a descriptive qualitative method. Having been collected by observation, recording, and interview, the data were transcribed, identified, and classified, then analyzed by description, quantification, and comparison. The findings were that, despite both employing a learner-centered approach; the interaction strategies are divergent due to different instructional goals. First, in the skill courses, the students' talking time is greater than the teachers' talking time, and the opposite fact exists in the content courses. Second, the interaction patterns in the skill courses indicate more student-active learning than in the content courses. Third, directive acts were performed more in the skill classes, and assertive acts in the content classes. Fourth, the native language was used more in the content than skill classes. The implication is that the interaction strategies should be varied following the pedagogical purposes to optimize the effectiveness of language teaching in an EFL context.